Quantitative value : a practitioner's guide to automating intelligent investment and eliminating behavioral errors + website - Gray, Wesley R. (Wiley, 2013)
Warren Buffett and Ed Thorp represent two spectrums of investing: one value driven, one quantitative. Where they align is in their belief that the market is beatable. This book seeks to take the best aspects of value investing and quantitative investing as disciplines and apply them to a completely unique approach to stock selection. Such an approach has several advantages over pure value or pure quantitative investing. This new investing strategy framed by the book is known as quantitative value, a superior, market-beating method to investing in stocks. Quantitative Value provides practical insights into an investment strategy that links the fundamental value investing philosophy of Warren Buffett with the quantitative value approach of Ed Thorp. It skillfully combines the best of Buffett and Ed Thorp weaving their investment philosophies into a winning, market-beating investment strategy. First book to outline quantitative value strategies as they are practiced by actual market practitioners of the discipline. Melds the probabilities and statistics used by quants such as Ed Thorp with the fundamental approaches to value investing as practiced by Warren Buffett and other leading value investors. A companion Website contains supplementary material that allows you to learn in a hands-on fashion long after closing the book. If you're looking to make the most of your time in today's markets, look no further than Quantitative Value.